Формування міського способу життя у другій половині ХІХ – на початку ХХ ст. (на матеріалах міста Харкова) - Боженко, Анастасія Олегівна; Bozhenko, A.O. (Харків: Харківський національний університет імені імені В.Н. Каразіна, 2018)
У дисертації досліджено основні аспекти формування міського способу життя у другій половині ХІХ – на початку ХХ ст. у Харкові. Схарактеризовано основні теоретичні засади вивчення модерного міста як феномена, розглянуто маркери модерності міст у Російській імперії, застосування теорії модернізації в межах міської історії. Розкрито головні аспекти в засадах створення модерного міського простору, зокрема забудови, розвитку комунальної інфраструктури, транспорту, комунікацій, мережі освітніх закладів та лікарень, показано динаміку їхніх змін. Простежено вплив індустріалізації на зміну міського ландшафту та соціальних стосунків. Окреслено співвідношення між центром та периферією міста, досліджено уявлення про просторові взаємовідносини частин Харкова, зокрема проблему входження нових територій до його складу. Увагу приділено також змінам у соціальному просторі міста, участі різних прошарків у формуванні міста та їхньому пристосуванні до нових умов, появі нових урбаністичних практик поведінки, пов’язаних із трансформуванням фізичного простору міста.
Forming of Urban Way of Life in the Second Half of the Nineteenth to the Early Twentieth Century (on the example of Kharkiv)
Bozhenko A. O. Forming of Urban Way of Life in the Second Half of the Nineteenth to the Early Twentieth Century (on the example of Kharkiv). – Qualification research paper, manuscript. Thesis for a Candidate Degree in History. – Speciality 07.00.01 – History of Ukraine. – V. N. Karazin Kharkiv National University. — Kharkiv, 2018. A modern era in the European history was marked by processes, which had changed society rapidly. Among them urbanization had played an essential role. Kharkiv was one of the cities, which was dynamically developing, and in early 20th century it became a local center. The actual value of the research is predetermined by increasing interest to the urban paradigm in Ukrainian historiography and moderate level of studying of the history of Ukrainian cities. The development of historiography was quite controversial. Despite the fact that in late 19th – early 20th centuries, the urban paradigm appeared both in the societies of Eastern and Western Europe and the intellectual backgrounds became synchronized, in the 20–30s of the 20th century these processes happened by different ways. The urban studies in Soviet historiography were suspended, while in Western humanities the new wave of urban research had begun by 1960. The first efforts to overcome the gap with the Western historiography were made in 1990, although Ukrainian historiography of urban studies still drops behind Western one. The main sources are written (documentation – journals of Kharkiv municipality, letters, laws – city charter, local decrees, statistics – materials of censuses of 1873, 1897, 1912 and 1916, official reference books – Pamyatnaya Knyzhka, Kharkiv calendars, guides, ego-source – memoirs by V. Karpov, K. Antonovych, D. Golitsyn, diaries by M. Vyshnevska), visual ones (postcards, photos) and cartographic sources (maps of the city). Methodology of the paper is based on the interdisciplinary character between history, urban studies and sociology. The main methods are critical analysis of sources, statistical analysis, comparative method and mapping.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects; стиль життя, урбанізація; Харків; модернізація; міський простір; міська історія; соціальна структура; повсякденні практики; інфраструктура; life style; urbanization; Kharkiv; modernization; city space; social structure; everyday practices; infrastructure; urban history